A historical sociolinguistic study on the conceptualisation and application of justice and law kwisizwe samaXhosa as documented in and extracted From SEK Mqhayi And W.W. Gqoba's selected writings - Ntshingana, Sanele (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2019)
This study seeks to investigate the original meanings contained in lexical terms relating to law (umthetho) and justice (ubulungisa) and their application in the precolonial Xhosa social society as they make appearance in SEK Mqhayi's novel Ityala lamawele (1914) and WW Gqoba's Isizwe esinembali, (1873-188/2015). Both of these works were written and initially published at the early point of contact of amaXhosa with the art of writing, and so are set in a 'traditional' setting (in the case of Mqhayi) and at early contact with European societies in Eastern Nguni region. This academic endeavour is undertaken by employing critical discourse theoretical framework. The purpose is to investigate the conceptualisation of law and justice amongst amaXhosa, and the extent to which this conceptualisation reflects the philosophical worldview of amaXhosa, as embedded in their language. The paper makes inferences about conceptualisation of law and justice in precolonial Xhosa social settings, and offers proposals on what this conceptual understanding could mean if its potential contribution to the contemporary understanding and application of law and justice in South Africa could be tapped into. The motivation for this study emanates from the current intellectual contestations in higher education that today's curricula present western knowledge systems as universal while marginalising indigenous epistemologies in teaching, learning and research practices. At the centre of these debates is how research, social and scientific thinking in humanities, is profoundly shaped by imported, racist, western "canonical" texts and theories. The arguments presented by various scholars argue that this enterprise firmly roots the collective imagination of students about the past and present in racist Eurocentric schematic frames, thus creating a problem of identity loss, and an intentional distortion of historical truths. The space for knowledge systems and experiences reflecting African memory and imagination is not only neglected, but distorted too. In this context, the study seeks to delve deeper into how African languages can be used to reconstruct knowledge systems that reflect African ways of understanding society as part of creating a curriculum that depicts "multiversal" ways of knowing (Tisani 2000; Santos, 2014). This study makes several findings, chief amongst which is that the legal and justice systems of the precolonial Xhosa society was both corrective as opposed to today's punitive court system that South Africa inherited, largely from the West. It seeks to prove that AmaXhosa's precolonial legal and justice system was focused more on reintegrating the offender back into society. The study further will show how the precolonial amaXhosa justice system was embedded in the concepts of ubulungisa (correct and re-intergrate) and isohlwayo (that which brings one to basics). Through discourse analysis of the early literary isiXhosa texts, the thesis discovers that the application of ubulungisa amongst amaXhosa back then was consistent with the philosophies embedded in the concepts. By exposing the collaboration networks between the white missionaries and the colonial administrators of the nineteenth century, the thesis will show how conspiracies were directed at erasing and displacing these indigenous epistemologies and to replacing them with colonial memories. To this end, missionary accounts, explorer diary entries and reports and early lexicographic material were produced and archived. Furthermore, this study makes a proposition that early written Xhosa texts be entrenched in the today's curricula in order inform the process of making sense of the social experiences and knowledge systems of the indigenous people of South Africa, from the precolonial-past to the present. Throughout the study, the thesis presents a proposition these early Xhosa texts be studied in relation to their intellectual contributions. This, it is hoped, will boldly challenge the canonised knowledge and racist assumptions about the African knowledge systems and experiences.
Keywords: Gqoba, William Wellington; Mqhayi, S. E. K.; Xhosa literature -- History and criticism; Law in literature; Justice in literature